What young graduates earn when they leave study - Park, Zaneta; Mahoney, Paul; Smart, Warren; Smyth, Roger (New Zealand Science Review, 2014)
​This report looks at the outcomes for young people who complete a qualification in the New Zealand tertiary education system. It looks at differences in incomes for different types of qualificationsPeople take tertiary education for many reasons and they use a range of information sources to help them make these choices. The information in this report is designed to add to the data available to people facing those decisions. Studying the earnings of graduates is also one way of looking at the contribution that the tertiary education system is making to New Zealand’s society and economy. So in turn this report contributes to an understanding of the value New Zealand receives for the investment made in tertiary education.